Tindak Pidana Penipuan Dalam Perspektif Fikih Jinayah - Gunawan, Hendra (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2018)
This paper discusses Fraud in the Jinayah Jurisprudence Perspective. The main problem in this article is how the perspective of jurisprudence against fraud, from here the authors formulate sub-problems namely how the terminology of fraud according to jurisprudence and how the punishment for the culprit according to jurisprudence jinyah.The method used in this article is descriptive qualitative, sourced from fiqh books and books related to the topics discussed in this article, the method of collecting literature study data.The author's findings in this article, that the form of fraud in the Criminal Law Act is almost similar to the fraud that exists in the book of Jurisprudence. In the text of the punishment for the perpetrators of fraud there is no standard rule that only emphasizes the punishment of the heaven, so the scholars stipulate that for the perpetrators of fraud are subjected to ta'zir penalties, namely the punishment handed over at the government's policy to decide.